The Perbandingan Algoritma Canny dan Algoritma Robert Pada Deteksi Tepi Kain Batik Khas Bengkulu - Nuri David Maria Veronika; Adelia, Serlina; Yuza Reswan; Muhammad Imanullah (JSAI (Journal Scientific and Applied Informatics), 2024)
This research discusses the comparative analysis of the Canny algorithm and Robert's algorithm in edge detection of Bengkulu cloth (Besurek) using the Matlab GUI interface. The selection of these two methods is to consider the balance between the quality of edge detection, noise resistance, and computational complexity. By comparing these two algorithms we can choose the algorithm that suits our needs. The purpose of this research is to make a comparison between the Canny algorithm and Robert's algorithm so as to produce the best algorithm in the edge detection process based on the number of white pixels produced. From the results of the datatest edge detection test totaling 32 images, the results of the percentage value obtained are the Canny algorithm obtaining 96.875% and the Robert algorithm 3.125%. So it can be concluded that the Canny algorithm is better in the process of edge detection based on the number of white pixels produced in each image.